Tunneled forehead island flap in medial orbital socket defect - Munjal, Manish; Munjal, Shubham; Chauhan, Swati; Arora, Vineeta; Singh, Ravinder Pal; Jain, Narinder; Jain, Dinesh; Kaur, Rubaldeep; Kaushal, Manik; Jeriwal, Sakshi; Budhiraja, Prachee; Ramdev, Aditi; et al. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
Orbital exenteration in debridement of rhino-sino-orbital Mucormycosis leaves a deep bony socket with or without a bony medial or an inferior party wall, depending on the extent of intervention. The eye brow sparing technique is likely to retain sufficient skin to line this orbital cavity. Prosthetics with fine resemblance to the contra lateral eye are designed and worn to achieve facial aesthetics. These artificial eyes are usually well modeled to sit in the socket. A breach on the medial wall in an individual a sequel to severe rhinitis, sneezing, cellulitis and prosthetic friction was reconstructed with a tunneled forehead flap. These tunneled flaps are single stage procedures unlike the conventional ones with excellent cosmesis.